2015
DOI: 10.1016/j.cropro.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of insecticide dose and herbivore density on tri-trophic effects of thiamethoxam in a system involving wheat, aphids, and ladybeetles

Abstract: a b s t r a c tWe assess how herbivore density and insecticide dose affects the tri-trophic interactions among thiamethoxam-treated wheat (Triticum sp.), Rhophalosiphum padi and the predatory Coleomegilla maculata DeGeer. In the first experiment 2nd and 4th instar C. maculata were fed aphids reared for 24 h on wheat plants treated with sub-lethal thiamethoxam soil drenches to assess the effect of insecticidal dose on the predator. In the second experiment a constant, sub-lethal thiamethoxam soil drench was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The control spiders received 1.0 ml of the acetone daily. We considered the insecticide concentration used to be sublethal to the spiders on the basis that it is sub-lethal to its target insects (Bredeson et al, 2015) and P. audax is many orders of magnitude larger. Moreover, we did not find the exposed spiders to experience any more mortality, tremors, paralysis or uncoordinated movements than the control spiders (see below for details of the procedures).…”
Section: Methodsmentioning
confidence: 99%
“…The control spiders received 1.0 ml of the acetone daily. We considered the insecticide concentration used to be sublethal to the spiders on the basis that it is sub-lethal to its target insects (Bredeson et al, 2015) and P. audax is many orders of magnitude larger. Moreover, we did not find the exposed spiders to experience any more mortality, tremors, paralysis or uncoordinated movements than the control spiders (see below for details of the procedures).…”
Section: Methodsmentioning
confidence: 99%
“…The authors emphasized that aquatic animals, including mollusks, are in direct contact with the contaminants present in the aquatic environment, and they can thus be a suitable model for future studies on the neuronal and behavioral consequences of neonicotinoid poisoning. In a recent study, BREDESON et al (2015) found clothianidin, a toxic metabolite of thiamethoxam, in aphids that were fed with wheat plants treated with thiamethoxam. This suggested that studies on the effects in herbivores of thiamethoxam residues and its metabolites are important.…”
Section: Thiamethoxammentioning
confidence: 99%
“…Populations of polyphagous predators vary by year (Chambers et al, 1983), tillage treatments (Rice and Wilde, 1991), and seed treatment prevalence (Seagraves and Lundgren, 2012). Additionally, the ability of species to control aphid populations may be negatively impacted by seed treatments (Bredeson et al, 2015). Direct observations, ELISA (enzyme-linked immunosorbent assay), gut dissections and PCR-based gut-content analysis have been employed to understand cereal aphid consumption by generalist predators.…”
Section: Introductionmentioning
confidence: 99%